Health-related quality of life in intensive care survivors: Associations with social support, comorbidity, and pain interference. - Anne Kathrine Langerud; Tone Rustøen; Milada Cvancarova Småstuen; Ulf Kongsgaard; Audun Stubhaug (PLoS ONE, 2018)
Background Experiences during a stay in the intensive care unit (ICU), including pain, delirium, physical deterioration, and the critical illness itself, may all influence survivors' health-related quality of life (HRQOL). However, few studies have examined the influence of social support, comorbidity, and pain interference on ICU survivors' HRQOL. Objectives To investigate possible associations between social support, number of comorbidities, and pain interference on HRQOL in ICU survivors. Methods ICU survivors responded to a survey 3 months (n = 118) and 1 year (n = 89) after ICU discharge. HRQOL was measured using the Short Form Health Survey-12 (v1), social support using the revised Social Provision Scale, pain interference using the Brief Pain Inventory-Short Form, and comorbidities using the Self-Administered Comorbidity Questionnaire. Results Physical and mental HRQOL were reduced at both 3 months and 1 year in ICU survivors compared with the general population. This reduction was more pronounced at 3 months for physical HRQOL, while a small reduction in mental HRQOL was not clinically relevant. Social support was statistical significantly positively associated with mental HRQOL at 3 months, while number of comorbidities was statistical significantly associated with a reduction in physical HRQOL at 3 months and 1 year and mental HRQOL at 1 year. Lastly pain interference was significantly associated with a reduction in physical HRQOL at 3 months and 1 year. Conclusions ICU survivors primarily report reduced physical HRQOL. Social support was positively associated with mental HRQOL, while number of comorbidities, and pain interference were all significantly associated with a reduction in HRQOL. Pain interference was associated with the largest reduction in HRQOL.